PENGARUH JUMLAH UANG BEREDAR, SUKU BUNGA BANK INDONESIA, DAN NERACA TRANSAKSI BERJALAN TERHADAP NILAI TUKAR RUPIAH PER-DOLAR AMERIKA TAHUN 2000-2017 - Sulistya, Imambang Eka; Budirahayu, Novita (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to analyze the factors thataffect the development of exchange rate (exchange rate) of Rupiah against US Dollar year 2000-2017. The type of data in this study is secondary data. Data used in the form of time series data year 2000-2017. Data were obtained from Bank Indonesia and Central Bureau of Statistics. Data analysis technique used is multiple linear regression analysis. The results show that: the money supply has a negative and significant effect on the US Dollar Exchange Rate 2000-2017, the interest rate of Bank Indonesia has a positive and significant effect on the US Dollar Exchange Rate 2000-2017, the current account balance has an effect negative and insignificant to the US Dollar Exchange Rate 2000-2017.